The Eksplorasi Hubungan Antara Self-Compassion dan Motivasi Belajar pada Siswa: Studi Bibliometrik - Wotan, Handhala Al Ashshidie (Maliki Interdisciplinary Journal, 2025)
Education plays a very important role in individual development, especially during adolescence, which is often a period of emotional and academic challenges. Self-compassion, which is the ability to treat oneself with kindness and without critical judgment, has been shown to contribute to improving students' emotional and academic well-being. This study aims to identify research trends on the relationship between self-compassion and learning motivation in students, using a bibliometric approach. The data analyzed include scientific publications related to this topic, taken from various international sources. The results of the analysis indicate that self-compassion has a positive effect on students' intrinsic motivation, which can help them manage academic stress and anxiety, increase emotional resilience, and strengthen motivation to learn. In addition, these findings also indicate that cultural context influences the way students apply self-compassion, especially in countries with a collectivist orientation such as Indonesia. This study suggests that self-compassion should be promoted in educational contexts to improve students' learning motivation, as well as providing directions for further research on effective interventions in developing self-compassion among students.